2015
DOI: 10.14260/jemds/2015/937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amniot Ic Fluid Volume and Its Relation to Perinatal Outcome

Abstract: BACKGROUND:Amniotic fluid is an indicator of placental function on the fetal development. The AFI is the most commonly used method of measuring amniotic fluid. AIMS: We aimed to study the amniotic fluid volume in pregnancies beyond 34 weeks of gestation and to evaluate the predictive value of amniotic fluid index (AFI <5cm) for adverse perinatal outcome in terms of labour inductions, fetal heart rate pattern, meconeum staining, caesarean section, Apgar score and NICU admissions. SETTING AND DESIGN: This was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The studies done by Tripathi et al, Bhagat et al and Casey et al, the AFI <5 cm was taken as oligohydroamnios at GA >34 weeks. 1,4,5 Regarding Non-stress test (NST), our study was similar to a study conducted by Bhagat et al in which they found that 32% women had non-reactive NST in oligohydramnios group compared to 9.7 % women in normal AFI group (AFI>5) with a p value of 0.002 which was statistically significant. 1 Similarly, in studies done by Sriya et al and Umber et al they found that 41.55% and 52.7% women had non-reactive NST respectively.…”
Section: Resultssupporting
confidence: 88%
“…The studies done by Tripathi et al, Bhagat et al and Casey et al, the AFI <5 cm was taken as oligohydroamnios at GA >34 weeks. 1,4,5 Regarding Non-stress test (NST), our study was similar to a study conducted by Bhagat et al in which they found that 32% women had non-reactive NST in oligohydramnios group compared to 9.7 % women in normal AFI group (AFI>5) with a p value of 0.002 which was statistically significant. 1 Similarly, in studies done by Sriya et al and Umber et al they found that 41.55% and 52.7% women had non-reactive NST respectively.…”
Section: Resultssupporting
confidence: 88%
“…Alterations in AFI have classically been considered as an indicator of fetal compromise. 6 So, the present study was conducted with the objective to study the association between amniotic fluid volume and perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…12 The drug hemodialysate (solcoseryl) effectiveness on liquor volume in intra uterine growth restriction (IUGR) babies and its outcome in form of APGAR score and health Damor J et al Int J Reprod Contracept Obstet Gynecol. 2023 Jul;12 (7): [2223][2224][2225][2226][2227][2228] status studies concludes that solcoseryl remains as a drug of choice in pregnancy with IUGR, after 28 weeks of gestation. 13 Current study aimed to determine whether an amniotic fluid level of 5cm or less can be predictor of adverse perinatal outcome in terms of fetal distress, birth weight, Apgar score and neonatal morbidity and mortality.…”
Section: Newer Drugsmentioning
confidence: 99%
“…Alterations in AFI have classically been considered as an indicator of fetal compromise. 7 Amniotic fluid is a clear, mildly yellowish coloured fluid contained in amniotic sac which is in circulation around the fetus. It has ennumerous functions which are important for the fetus and its development inutero.…”
Section: Introductionmentioning
confidence: 99%